Innovative irrigation system for agriculture - Fairus Nasirin, Muhammad Affiq Haiqal; Mohammad, Nurul Nadia; Nordin, Siti Aminah; M. Zin, Nor Affida (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
One of the main challenges that many farmers and gardeners face is the need to carry heavy watering cans or repeatedly fetch water from sources to irrigate their plants. This task is physically demanding and can leave them feeling exhausted, requiring significant energy. For example, elderly individuals may experience joint pain and body aches due to the repetitive strain, while younger adults may be too busy with their jobs to consistently water their houseplants. As a result, plants may suffer from insufficient watering and eventually begin to wither and die. Therefore, the irrigation system offers a practical solution by streamlining the watering process and reducing the physical effort required. To address these issues an innovative irrigation system for agriculture was developed. The water pump system is designed to distribute water efficiently across the entire plantation equipped with many sensors like pH sensors, moisture sensor and water level sensor that make the system become more efficient. Additionally, the system incorporates effective water storage and distribution mechanisms, ensuring a consistent and reliable water supply for the plants. This solution not only saves energy and time but also promotes healthier and more sustainable plant growth that significant advancement in optimizing agricultural practices.